Carbon nanotubes-polymer based highly stretchable piezoresistive sensors with linear response and tunable sensitivity - Tadakaluru,S. (American Scientific Publishers, 2015)
Copyright © 2014 American Scientific Publishers All rights reserved. Polymer and nanomaterials based piezoresistive sensors have acquired significant attraction because of their multifunctional applications. Though few researchers achieved higher strain limit than the commercial metallic strain sensors (5%), the response curves of those sensors were highly nonlinear. The highest degree of nonlinearity of sensor's response curves is a serious factor that may limit practical applications. In this present work we report a kind of strain sensors made by coating, multi-walled carbon nanotubes on natural rubber tubes. The relative change in the resistance of the sensors increased linearly with the applied stain. These polymer based multi-walled carbon nanotubes sensors showed greater linear response as well as higher strain limit (720%). By adding graphite flakes to the multi-walled carbon nanotubes the sensitivity of the sensors was varied. The effect of the cnt-graphite weight ratio on sensor's sensitivity and strain limit was also investigated.